2018
DOI: 10.1016/j.athoracsur.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A Tumor Necrosis Factor-α and Hypoxia-Induced Secretome Therapy for Myocardial Repair

Abstract: Our data suggest that after MI, rBM-MSCs secrete paracrine factors in response to TNF-α and hypoxia that work together to manipulate the microenvironment and decrease inflammation. In addition, these signaling factors trigger angiogenic and migratory effects at the site of the infarct to promote myocardial healing and improve the cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 21 publications
4
32
0
3
Order By: Relevance
“…It has been well elucidated that rat BMSCs can secrete paracrine factors including VEGF-1 to trigger angiogenic and migratory effects at the site of the infarct to promote myocardial healing and to improve the cardiac function [39]. In the current study, we also found that the level of VEGF and MVD in the infarct zone had a signi cant increasement after BMSCs transplantation, indicating that paracrine effect plays an essential role in BMSCs tissue repair and angiogenesis.…”
Section: Discussionsupporting
confidence: 68%
“…It has been well elucidated that rat BMSCs can secrete paracrine factors including VEGF-1 to trigger angiogenic and migratory effects at the site of the infarct to promote myocardial healing and to improve the cardiac function [39]. In the current study, we also found that the level of VEGF and MVD in the infarct zone had a signi cant increasement after BMSCs transplantation, indicating that paracrine effect plays an essential role in BMSCs tissue repair and angiogenesis.…”
Section: Discussionsupporting
confidence: 68%
“…Currently, a number of studies have shown that transplanting MSCs in vivo can increase injured site closure by secreting paracrine factors, which are beneficial to the healing of damaged tissue (Table 3). For example, after myocardial infarction, rat BMSCs secrete paracrine factors (TGF-β, FGF-2, angiopoietin-2, VEGF-1) to trigger angiogenic and migratory effects at the site of the infarct to promote myocardial healing and improve the cardiac function [1]. In a NOD/SCID mouse model, the transplanted BMSCs secreted nerve growth factor (NGF), HGF, and anti-inflammatory molecules (IL-10, IL1-RA), which contribute to the prevention of apoptosis and increase cell proliferation in the damaged liver [84].…”
Section: Mechanisms Of Bmscs In Tissue Repairmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) represent an important source for cell therapy in regenerative medicine. MSCs have shown promising results for repairing damaged tissues in various degenerative diseases, both in animal models and in human clinical trials [1,2,3,4,5,6]. MSCs have a homing ability, meaning that they can migrate into injured sites, and they possess the capacity to differentiate into local components of injured sites and the ability to secrete chemokines, cytokines, and growth factors that help in tissue regeneration [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…TNFR1 signaling can also increase PGE2 secretion by inducing COX2 expression in mouse or human BM-MSCs, which in turn reprograms host macrophages to increase IL-10 production thus inhibiting inflammation in a mouse sepsis model and experimental allergic conjunctivitis ( 117 , 118 ). In addition, it has been shown that other immunosuppressive molecules, growth factors, and chemokines such as TSG-6, TGFβ, and IL-8 were produced by TNF-primed MSCs to attenuate the symptoms in diseases including EAE, myocardial infarction, ischemic hind limb, and cutaneous wound probably via TNFR1 signaling pathway ( 122 , 135 , 139 , 141 ). TNF can also induce TNT formation between iPSC-derived MSC and cardiomyocytes for mitochondria transfer to attenuate the damage in mouse anthracycline-induced cardiomyopathy, which is regulated by TNF/NFκB/TNF-IP2 signaling pathway ( 129 ).…”
Section: Tnf Regulation Of Msc Efficacy On Autoimmune and Inflammatormentioning
confidence: 99%